Association between age at first reported e‐cigarette use and subsequent regular e‐cigarette, ever cigarette and regular cigarette use. (12th January 2021) - Conner, Mark; Grogan, Sarah; Simms‐Ellis, Ruth; Cowap, Lisa; Armitage, Christopher J.; West, Robert; Marshall, Anna‐Marie; Siddiqi, Kamran
Abstract: Background and aims: Association of electronic cigarette use and subsequent smoking has received considerable attention, although age of first use has not. This study tested differences in regular (e‐cigarettes, cigarettes) and ever (cigarettes) use between e‐cigarette user groups: early versus never users, late versus never users, early versus late users and effects of controlling for covariates. Design: Prospective study with 12‐ and 24‐month follow‐up of e‐cigarette/cigarette ever/regular use with data from an intervention. Setting: Forty‐five schools in England (Staffordshire and Yorkshire). Participants: Never smokers (3289 13–14‐year‐olds) who were part of a cluster randomized controlled trial. Measurements: The sample was divided into groups of e‐cigarette users: early users (at 13–14 years), late users (at 14–15 years) and never users (at 13–14 and 14–15 years). Dependent variables were self‐reported regular e‐cigarette and cigarette use and ever cigarette use at 15–16 years. Covariates were assessed. Findings: Early and late users compared with never users were significantly more likely to be regular e‐cigarette users [early: odds ratio (OR) = 9.42, 95% confidence interval (CI) = 5.38, 16.49, P  < 0.001; late: OR = 6.89, 95% CI = 4.11, 11.54, P  < 0.001], ever cigarette users (early: OR = 7.96, 95% CI = 6.02, 10.53, P  < 0.001; late: OR = 5.13, 95% CI = 3.85, 6.84, P  < 0.001) and regular cigarette users (early: OR = 7.80, 95% CI = 3.99, 15.27, P  < 0.001; late: OR = 4.34, 95% CI = 1.93, 9.77, P  < 0.001) at age 15–16 years. Late users compared with early users had significantly lower rates of ever use of cigarettes at 15–16 years (OR = 0.48, 95% CI = 0.35, 0.66, P  < 0.001), although this difference was non‐significant at 12 months after first use of e‐cigarettes (OR = 0.89, 95% CI = 0.64, 1.25, P  = 0.498). Controlling for covariates did not change the findings. Conclusions: Adolescents in England who report using e‐cigarettes at age 13–14 years have higher rates of subsequently initiating cigarette use than adolescents who report using e‐cigarettes at age 14–15 years, a difference that may be attributable to a longer period of time to initiate cigarette use in former group.